Pharmacological Rationale for Targeting IL-17 in Asthma - Rahmawati, Siti Farah; te Velde, Maurice; Kerstjens, Huib A. M.; Dömling, Alexander S. S.; Groves, Matthew Robert; Gosens, Reinoud (Frontiers in Allergy, 2021)
Asthma is a respiratory disease that currently affects around 300 million people worldwide and is defined by coughing, shortness of breath, wheezing, mucus-overproduction, chest tightness, and expiratory airflow limitation. Increased levels of IL-17 have been observed in sputum, nasal and bronchial biopsies, and serum of asthma patients compared to healthy controls. Patients with higher levels of IL-17 have a more severe asthma phenotype. Biologics are available for Th2-high asthmatics, but the Th17-high subpopulation has a relatively low response to these treatments, rendering it a rather severe asthma phenotype to treat. Several experimental models suggest that targeting the IL-17 pathway may be beneficial in asthma. Moreover, as increased activation of the Th17/IL-17 axis is correlated with reduced ICS sensitivity, targeting the IL-17 pathway might reverse ICS unresponsiveness. In this review, we present and discuss the current knowledge on the role of IL-17 in asthma and its interaction with the Th2 pathway, focusing on the rationale for therapeutic targeting of the IL-17 pathway.